Asuhan Kebidanan Berbasis Spiritual - Khoirul Waroh, Yuni; Latifah, Anik; Hubaedah, Annah (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2022)
The birth process is a very valuable event for a mother where there are many mixed feelings experienced by the mother and other family members. The spiritual dimension is an integral aspect of human life that gives meaning to an individual's overall existence, and spiritual needs are commonly experienced by clients with sudden illness, loss, chronic conditions, and life-limiting conditions, including childbirth. One of the efforts to maintain mental health during the delivery process is to provide spiritual-based care. The research method used is the literature review method which was collected through the data base of the Journals of Pubmed, Medline, Pro Quest and Cochrane Lybrary. The result of the literature review is that there is empirical evidence of spiritually based midwifery care on reducing anxiety during pregnancy and preoperative cesarean section, reducing pain during labor, and improving fetal well-being.